2016
DOI: 10.1016/j.colsurfa.2016.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Probing the organization of fulvic acid using a cationic surfactant

Abstract: The organization of Suwannee River Fulvic Acid (SRFA) is investigated through the interaction of SRFA with a cationic surfactant molecule (Dodecyl-trimethylammonium chloride (DTAC)). Turbidity measurements, Dynamic light scattering, electrophoretic mobility, surface tension, and cryo-transmission electron microscopy are combined to describe the SRFA/DTAC molecular structures thus obtained. Increasing DTAC concentration, fulvic acid-rich unilamellar vesicles, globules, aggregates of globules, disks, DTAC-rich u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Previous studies on the interactions between humic substances and cationic surfactants were interested in two main aspects: (i) the fate of the surfactant molecule introduced in the natural environment either as an organic contaminant through wastewater discharge (Koopal et al 2004;Ishiguro et al 2007;Hakim and Kobayashi 2019) or as a detergent for the remediation of aquifers and contaminated soils (Harwell et al 1999;Mao et al 2015); (ii) the chemical structure of the humic substances, the surfactant being used as a probe of amphiphilic properties of humic matter or as a titrant of the total amount of carboxyl functional groups (Tombacz et al 1988;De Nobili et al 1990;Yee et al 2006;Shang and Rice 2007;Chaaban et al 2016). Overall, the reports concur that the binding of the cationic surfactant to the humic substance initially proceeds through strong electrostatic interactions between the carboxylic groups of humic matter and the positively charged head groups of the surfactant.…”
Section: Complexation Of Srha With Alkyltrimethylammonium Cationic Surfactantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies on the interactions between humic substances and cationic surfactants were interested in two main aspects: (i) the fate of the surfactant molecule introduced in the natural environment either as an organic contaminant through wastewater discharge (Koopal et al 2004;Ishiguro et al 2007;Hakim and Kobayashi 2019) or as a detergent for the remediation of aquifers and contaminated soils (Harwell et al 1999;Mao et al 2015); (ii) the chemical structure of the humic substances, the surfactant being used as a probe of amphiphilic properties of humic matter or as a titrant of the total amount of carboxyl functional groups (Tombacz et al 1988;De Nobili et al 1990;Yee et al 2006;Shang and Rice 2007;Chaaban et al 2016). Overall, the reports concur that the binding of the cationic surfactant to the humic substance initially proceeds through strong electrostatic interactions between the carboxylic groups of humic matter and the positively charged head groups of the surfactant.…”
Section: Complexation Of Srha With Alkyltrimethylammonium Cationic Surfactantsmentioning
confidence: 99%
“…A similar trend has been reported for the Suwannee River fulvic acid/DTAC system. In that case, the minimum is interpreted as the result of a rearrangement of fulvic acid upon neutralization with the cationic surfactant (Chaaban et al 2016). Indeed, the initial neutralization of external sites of humic matter by the cationic surfactant enhances the hydrophobicity of the complex, that then undergoes a structural rearrangement turning inside-out some previously unattainable negatively charged sites (Sieliechi et al 2008).…”
Section: Complexation Of Srha With Alkyltrimethylammonium Cationic Surfactantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Klencsaŕ and Köntös 15 completed the EPR analysis of Fe 3+ and Mn 2+ complex sites in FA, which can be used to track and characterize the structural changes in FA complexes under different conditions and chemical reaction conditions. Chaaban et al 16 showed that a major component of Suwannee River FA is an individual, negatively charged amphiphile with a molecular size similar to that of dodecyl trimethyl ammonium chloride.…”
Section: Introductionmentioning
confidence: 99%